Structural studies on magnesium calcium tellurite doped with Eu2+ and Dy3+ - Alias, Nur Shahira (Malaysian Solid State Science and Technology Society, 2009)
The samples of phosphor material based on alkali earth tellurite, doped with rare earth have been prepared using solid state reaction method. The samples are with the composition in mol %: xMgO-(30-x)CaO-70TeO2 with 0=x=30 mol%, and have been doped with Eu2O3(2mol%) and Dy2O3(1mol%). The structure of the samples have been investigated by means of X-Ray Diffraction, Raman and Infrared spectroscopy. The xray diffraction results show that two phase are observed in the samples, which is MgTe2O5 and CaTe2O5 phase. Raman spectroscopy studies show that the vibrations of the samples are identical with the a-TeO2 vibrations, with a shift about 40-50cm-1. Strong bands are observed located at around 435, 616, 689, 785, and 807cm-1. As the concentration of the modifier, MgO and CaO increased, the coordination of TeO4 are transform from the corner sharing, a-TeO2 structure to the edge sharing, ÃŸ-TeO2 structure. It is also indicated that the increasing of MgO contribute to the increasing of symmetry vibration of TeO4 molecule, s(TeO4), while the addition of CaO increased the asymmetry vibration of TeO4 molecule, as(TeO4). The comparison between Raman and IR spectra is also include to identify the mode vibration of the samples.